2020
DOI: 10.20471/acc.2020.59.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Independent Factors for Poor Prognosis in Young Patients with Stage I-III Breast Cancer

Abstract: breast cancer is the most common malignancy in the population of women under 40 years of age. young age is an independent factor for poor prognosis. In this research, we tried to establish other factors for poor prognosis in stage I-III breast cancer. The following parameters were observed: tumor size, lymph node status, histologic grade, hormonal receptor status, Ki-67 prognostic index, her2 neu status, histologic type of the tumor, local recurrence and metastases. Logistic regression was used to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Age is a well-known prognostic factor for many tumors. [21][22][23] In patients with osteosarcoma, Hagleitner et al demonstrated that the 5-year OS rate for patients aged 20-40 years was 33.3% while 70.6% in ≤14 years old and 52.5% in 15-19 years old in a retrospective study of 102 osteosarcoma patients. 24 Moreover, Tsuchie et al compared the prognosis of primary osteosarcoma in younger and older patients based on a cut-off age of 40 and concluded that the older patients showed a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Age is a well-known prognostic factor for many tumors. [21][22][23] In patients with osteosarcoma, Hagleitner et al demonstrated that the 5-year OS rate for patients aged 20-40 years was 33.3% while 70.6% in ≤14 years old and 52.5% in 15-19 years old in a retrospective study of 102 osteosarcoma patients. 24 Moreover, Tsuchie et al compared the prognosis of primary osteosarcoma in younger and older patients based on a cut-off age of 40 and concluded that the older patients showed a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…also showed that non-ductal or lobular histological type (such as mucinous, medullary, tubular or metaplastic carcinoma) compared to invasive ductal or lobular type was associated with a lower risk of ALNM ( 38 , 39 ). A study showed that compared with older patients, young patients are more likely to have regional lymph node and distant metastasis ( 40 ). Other studies have considered age as an independent predictor of ALNM ( 27 29 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of different prognostic and predictive factors, our ability to predict breast cancer prognosis in each individual patient is limited ( 29 ). Therefore, identifying reliable and efficient prognostic factors remains a major research effort in order to avoid overtreating low-risk patients and enhance the efficacy of adjuvant treatment for those with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%